Wildmentor-an Interactive Digital Encyclopedia of Fauna and Flora of Bangladesh - Islam, Safiqul; Saquib, Shah; López, Alejandro Izquierdo; Hausmann, Alexander E; Sultana, Rukshana; Hossain, Abu NM; Rahman, Habibur; Alim, Abdul; Hossain, Monwar; Naser, M Niamul; Päckert, Martin (Bangladesh Journal of Zoology, 2021)
Abstract not available Bangladesh J. Zool. 49(1): 161-167, 2021